Integrated into the research: the embedded librarians - Torres-Salinas, Daniel (Anuario ThinkEPI, 2011)
With desktop availability of electronic publications, researchers have reduced significantly their visits to libraries. A new role for librarians is described: their integration into academic departments, becoming part of research teams. They would perform tasks such as information searching for projects, database management, uploading documents to repositories, writing reports, building and maintaining web sites, preserving datasets, etc.
Keywords: Librarians; Information scientists; Evolution; New duties; Collaboration; Participation; University; Research.